A targeting theranostics nanomedicine as an alternative approach for hyperthermia perfusion. (November 2018) - Sun, Tao; Zhang, Guangping; Wang, Qingbing; Chen, Qinjun; Chen, Xinli; Lu, Yifei; Liu, Lisha; Zhang, Yu; He, Xi; Ruan, Chunhui; Zhang, Yujie; Guo, Qin; et al.
Abstract: Real-time monitoring drug-release is often regarded crucial in theranostics nanomedicine design, since it provides precise establishment of spatio-temporal activation of the drug-release in vitro and in vivo . A symmetrical self-immolative drug-dye conjugation (DDC) prodrug is developed in this study with disulfide bond as the trigger. The prodrug can be escorted by targeting PEG-PLGA micelles and hereby accumulated in the tumor by both active and passive targeting effect. Glutathione (GSH) with higher concentration in the tumor microenvironment can readily cleave the disulfide bond to initiate a subsequent decomposition of DDC, where the drug and dye can be released simultaneously in a strict one-to-one mode. Upon the disintegration, the "Turned-On" probe can emit near-infrared (NIR) fluorescence, with the aim of providing accurate and real-time information for the prodrugs' activation and biodistribution in vivo in a non-invasive way. Furthermore, the released dye can meanwhile act as a photothermic sensitizer, which can in-situ assist a deep penetration for the released drug in the tumor tissue with enhanced therapeutic efficiency. This "babysitting" strategy provides new reference for designing versatile theranostic nanomedicines for preclinical evaluations and an alternative approach for hyperthermia perfusion in clinic.